Seasonal effects on seminal attributes in Murrah bulls under Bangalore agroclimatic conditions - BHAT, VINOD; HONNAPPA, T G; DUBEY, B M (The Indian Journal of Animal Reproduction, 2023)
The present study was undertaken to know the seasonal influence on various seminal attributes, in Murrah bulls. Data included 4,446 ejaculates over a period of 7 years. The seminal volume, mass activity and number of semen straws produced were significantly high (P<0.05) during monsoon.,The sperm concentration was highest (943.77±22.02 106/ml.) in summer. The initial motility and post thaw motility were not affected by different seasons. Monsoon season was most favourable for production of quality semen, followed by summer and winter.